Perspectives of Teachers Towards Students with Diverse Disability: A Case of Special School in Kailali District - Bhatta, Narayan Datta (Far Western Review, 2023)
Working with differently able children in the classroom is challenging in under-resourced contexts for Nepal teachers. This study explores teachers’ perceptions toward managing the diversity of the students in terms of disability, teaching-learning activities, assessment practices, and interpersonal skills in a special school. This qualitative study adopts a case study design. In-depth Interviews, focus group discussions (FGD), and participant observation were the major methods for data collection. Six teachers (three ordinary and three with disability) for FGD and two key informants (head teacher and chairperson) were selected purposively for in-depth Interviews from a special school located at Attariya in Kailali district. The study shows that teachers have positive perceptions toward disabilities, especially teachers with disability. Teachers have invested efforts in managing diversity in instruction and in assessment; however, it is challenging due to the traditional approach of teaching and evaluation, lack of training and resources, and the gap between policies and practices. The study further indicates that teachers’ positive perceptions and extracurricular activities are crucial for developing students’ interpersonal skills.